(untitled) (World Bulletin of Public Health, 2024)
The article presents data on the quality of life of dermatovenereological patients before and after the course of treatment. The issues of the possibilities of using the international quality of life questionnaire MOS-SF-36 for assessing the criteria for the quality of inpatient care for dermatovenereological patients, as one of the important indicators of quality management of hospital care for this category of patients, are considered, the effect of treatment of patients with skin diseases in inpatient settings on improving their quality of life is shown